MULTI-CRITERIA OPTIMIZATION OF CIVIL SHELTERS DESIGN IN UKRAINE TAKING INTO ACCOUNT ISRAELI EXPERIENCE - Малік, Т. В.; Ковальов, Ю. М.; Калашнікова, В. В.; Нерушева, В. М. (Art and Design, 2023)
The aim of the work is to determine the focus group and initial data, optimization criteria, and limitations, systematize the typology of shelters and note their main characteristics, develop an optimization strategy, and substantiate recommendations for creating shelters in Ukraine using Israeli experience. The methodology is based on the concepts of a complex open system and a system approach and includes the methods of system analysis, analysis according to the "income matrix" and "cost matrix" (according to the criteria of Laplace and Wald), comparative analysis, adapted for solving the tasks of defining a focus group and needs of the target consumer, criteria for selecting sources of information, formation of the optimization task, optimization criteria, limitations and optimization strategy. The results. Focus groups and their needs for shelters of various types have been defined for the civilian population. Three types of such shelters are defined. Correlations between needs, constructive and design solutions of shelters are substantiated. The choice of the reference country – Israel, which is constantly under threat of shelling and terrorist acts, is justified. The Israeli experience of building various types of shelters is analyzed. The optimal options for design, construction, and technological solutions were chosen, taking into account the needs of the civilian population of Ukraine. The scientific novelty consists in the correct formulation of the problem of constrained optimization, finding correlations between the needs of the focus group and constructive and design solutions, the involvement and analysis of foreign experience, the strategy of multi-criteria constrained optimization, recommendations on the adaptation of this experience to threats and other features that take place in Ukraine during the war. Practical significance. Recommendations are provided for creating a system of various shelters that complement each other, meeting the diverse needs of the focus group. In particular, it is advisable to use: for the internal environment (mamad, miklat, complex shelter); for the external environment (shelter buildings); for combined use (mamak, fortification of buildings of the TAMA 38 type, fortification of social important objects). The need to improve the organization of construction and financing of works has been determined, in particular, it is advisable to use prefabricated industrial structures and more flexible financing schemes more widely, for example, "capital" shelters – at the expense of the state budget, miklats, and shelter structures – at the expense of local communities, mamadas, and complex shelters – at the expense of account of the population with the provision of relevant benefits.